Umayyad legacies : medieval memories from Syria to Spain - Borrut, Antoine.; Cobb, Paul M., 1967- (Islamic History and Civilization, 2010)
The Umayyads, the first dynasty of Islam, ruled over a vast empire from their central province of Syria, providing a line of caliphs from 661 to 750. Another branch later ruled in al-Andalus - Islamic Spain - from 756 to 1031, ruling first as emirs and then as caliphs themselves. This book is the first to bring together studies of this far-flung family and treat it not as two unrelated caliphates but as a single enterprise. Yet for all that historians have made note of Umayyad accomplishments in the Near East and al-Andalus, Umayyad legacies - what later generations made of these caliphs and their achievements - are poorly understood. Building on new interest in the study of memory and Islamic historiography and including interdisciplinary perspectives from Arabic literature, art, and archaeology, this book highlights Umayyad achievements and the shaping of our knowledge of the Umayyad past.